Lymphoadenopathies caused by Bartonella henselae - V.S. Zhukovskiy; O.V. Prokopiv; I.R. Trutyak; M.V. Pankiv (Medičnì Perspektivi)
Bartonella henselae is the causative agent of cat scratch disease, the main manifestation of which is lymphadenopathy, but it can manifest as bacillary angiomatosis, injury to internal organs, joints, eyes, heart, kidneys. This disease is often encountered in the practical work of doctors, especially with an atypical form of the course, which occurs in 20% of adult patients. Often the disease is undiagnosed, mimicking lymphadenopathies caused by tumors of soft tissues and bones or other bacterial pathogens. The purpose of the work was to analyze clinical cases of cat scratch disease by the results of inpatient records data based on the leading clinical symptom – lymphadenitis, to summarize literature data related to morbidity, features of the clinical course and treatment of this disease. The description of two clinical cases of cat scratch disease in adult women aged 19 and 59 is given. The typical course of the disease in one of them at the beginning of the disease, was manifested by symptoms of general intoxication, fever, an increase of lymph nodes in the neck and axillary area, which coincided in time with the previously diagnosed bacterial angina. The diagnostic search ended with the set diagnosis and surgical operation three months after the onset of clinical manifestations of the disease. In the second case, a subfebrile body temperature, a painful lymph node in the right axillary area for 3 weeks were the reason to perform an invasive surgery twice for diagnosed bacterial process of unknown etiology. The reasons for late diagnosis and treatment of cat scratch disease in our patients were insufficient collection of epidemiological anamnesis, lack of vigilance of doctors, first of all, surgeons, regarding the clinical manifestations of the disease and late examination to find out the etiological factor of the disease. An elevated titer of IgM antibodies to Bartonella henselae 1:160 and 1:140 in two cases was the basis for confirming cat scratch disease. Based on the results of the literature analysis, an overview of typical and atypical manifestations of cat scratch disease, its diagnosis and treatment is presented. Bartonella henselae infection should be considered in all cases of lymphadenitis of unknown etiology, accompanied by high temperature, intoxication syndrome and a long course. In order to prevent the development of purulent complications and to avoid unreasonable invasive procedures, it is important to make a timely diagnosis and carry out appropriate antibacterial treatment at the initial stage of the manifestation of clinical symptoms of cat scratch disease.